Pemberdayaan Petani Melalui Penerapan Teknologi Pertanian Ramah Lingkungan di Desa Sembungharjo - Sadiqin, Amin; Prasetyo, Hendra Dwi; Komariyah, Fitri (PUTRA JAWA PUBLISHER, 2024)
This research aims to improve the welfare of farmers in Sembungharjo Village through the application of environmentally friendly agricultural technology. This program involves training and mentoring farmers in the use of organic fertilizers, efficient irrigation techniques, and integrated pest management. The research results show an increase in agricultural productivity by 25% and a reduction in production costs of up to 15% after implementing this technology. Additionally, there has been an increase in environmental awareness among farmers which contributes to the sustainability of agricultural practices. The application of environmentally friendly agricultural technology has proven effective in empowering farmers and supporting sustainable agriculture.